Terms of Classical Ottoman Music in the Divan of Ahmed Hatem Bjelopoljak - Ćatović, Alena; Nametak, Fehim (Prilozi za orijentalnu filologiju, 2017)
Ahmed Hatem Bjelopoljak (Akovalızâde), an 18th century Ottoman/Bosniac intellectual, was a very versatile poet who wrote semantically saturated and multi-faceted poetry in three languages – Arabic, Ottoman Turkish and Persian. Although dominated by Islamic mysticism his lyrics are also interweaved with other sources of influence, the most interesting being the classical Ottoman music. This paper analyzes the relation between the music and the Hatem`s poetry – written in three different genres: qasida, gazel and sharqiye – which is, for example, shown through constant references to the names of the instruments and the classical Ottoman music modes (maqam). This analysis contributes to the overall valorization of the Hatem`s poetry, it discloses his special interest for music and emphasizes the relation between music and literature. It also suggests a possibility that the Hatem’s poetry was written with an intention to be accompanied by music instruments.